SQ3R method assisted by ethnomathematics-oriented student worksheet: The impact of mathematical concepts understanding. Issue 1 (February 2021) - Suherman,; Rahmadani, Nanda Ayu; Vidákovich, Tibor; Mujib,; Fitria, Nike; Sari Putri, Nur Islam; Addarojat, Muhammad Rofi'uddin; Priadi, Maskur
Abstract: This study was aimed to determine the impact of the SQ3R method assisted by ethnomathematics-oriented student worksheets on students' ability to understand mathematical concepts which compared with the SQ3R method without ethnomathematics-oriented student worksheets. The research method used was quasi-experimental research. The SQ3R method assisted by an ethnomathematics-oriented student worksheet was implemented in the experimental class while the control class was treated by the SQ3R learning method. The design of this study was the pretest-posttest control group design to see the effectiveness of the SQ3R method assisted by ethnomathematics-oriented student worksheets. A cluster random sampling technique was used to determine the sample of the study. The data collection technique employed in this study was an essay test to measure the students' ability to understand mathematical concepts. The results showed that the SQ3R method assisted by ethnomathematics-oriented student worksheet was more effective toward students' mathematical concepts understanding compared to the SQ3R learning method. The application of learning provided better results in increasing students' ability to understand mathematical concepts.